Repeat-dose toxicity study of human umbilical cord mesenchymal stem cells in cynomolgus monkeys by intravenous and subcutaneous injection - Pan, Wei; Gu, Liqiang; Yang, Hongzhong; Xu, Cong; Yang, Zhengbiao; Lu, Qijiong; Shi, Yuhua; Zhang, Lili; Shao, Jinjin; Chen, Yunxiang; Pan, Xin; Wu, Feifei; et al. (Frontiers in Cell and Developmental Biology, 2023)
Human umbilical cord mesenchymal stem cells (hUC-MSCs) are proposed for the treatment of acute lung injury and atopic dermatitis. To advance hUC-MSC entry into clinical trials, the effects of hUC-MSCs on the general toxicity, immune perturbation and toxicokinetic study of hUC-MSCs in cynomolgus monkeys were assessed. hUC-MSCs were administered to cynomolgus monkeys by intravenous infusion of 3.0 × 106 or 3.0 × 107cells/kg or by subcutaneous injection of 3.0 × 107cells/kg twice a week for 3 weeks followed by withdrawal and observation for 6 weeks. Toxicity was assessed by clinical observation, clinical pathology, ophthalmology, immunotoxicology and histopathology. Moreover, toxicokinetic study was performed using a validated qPCR method after the first and last dose. After 3rd or 4th dosing, one or three the monkeys in the intravenous high-dose group exhibited transient coma, which was eliminated by slow-speed infusion after 5th or 6th dosing. In all dose groups, hUC-MSCs significantly increased NEUT levels and decreased LYMPH and CD3+ levels, which are related to the immunosuppressive effect of hUC-MSCs. Subcutaneous nodules and granulomatous foci were found at the site of administration in all monkeys in the subcutaneous injection group. Other than above abnormalities, no obvious systemic toxicity was observed in any group. The hUC-MSCs was detectable in blood only within 1 h after intravenous and subcutaneous administration. The present study declared the preliminary safety of hUC-MSCs, but close monitoring of hUC-MSCs for adverse effects, such as coma induced by intravenous infusion, is warranted in future clinical trials.